Taking an HPV vaccine research-tested intervention to scale in a clinical setting. Issue 5 (7th February 2018) - Hopfer, Suellen; Ray, Anne E; Hecht, Michael L; Miller-Day, Michelle; Belue, Rhonda; Zimet, Gregory; Evans, W Douglas; McKee, Francis X
Abstract: Research tested interventions are seldom ready for wide spread use. Successful intervention adaptation to clinical settings demands an iterative process with target audience feedback. We describe the adaptation process of implementing an NCI research tested HPV vaccine intervention, Women's Stories, to a community clinic context (Planned Parenthood). Five phases are described for the adaptation of content and the development of a health kiosk intervention delivery system: (a) informant interviews with the target audience of young adult, predominantly African-American women, (b) translating HPV vaccine decision narratives into prevention messages, (c) health kiosk interface design, (d) conducting a usability study of the health kiosk intervention product, and (e) conducting a waiting room observational study. Lessons learned and challenges in adapting prevention interventions to clinical settings are discussed. Abstract : Taking evidence-based prevention programs to scale involves fast-tracking a series of steps that serve critically important goals for advancing the translation of science into clinical practice settings.